Pengembangan Variasi Latihan Shooting Menggunakan Model Latihan Drills For Game-Like-Situation pada Kelompok Usia 15-18 - Hasibuan, Ali Sutan; Novita, Novita; Manalu, Nimrot (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to develop variations in shooting training using drills for game-like situation training models in the 15-18-year-old group in Medan City. This research method is development research (R&D). The place of this research was carried out in Medan City. The subjects of this research were basketball athletes at the Medan City Club, totaling 20 people for the small group test and 30 for the large group test. Data collection techniques include questionnaires, documentation, and observation. Research results: The development of drills for game-like-situation training models for athletes in the Health and Recreation physical education study program was carried out by exploring potential problems from athletes and coaches, then collecting data from research journals to see the novelty and variations of training, then the product was developed on several parts; The feasibility of producing the results of the assessment of 20 basketball athletes regarding the drills for game-like-situation training model for the 15-18 year age group gave a total percentage of 77.63%. The results of the assessment of 30 basketball athletes on the drills for game-like-situation training model for the 15-18 year age group gave a total percentage of 84.78%. The effectiveness test results obtained a sig value of 0.000 < 0.05, so it is in accordance with the basis for decision-making in the paired samples T-Test. In conclusion, there is a difference in the drills for the game-like-situation training model for the 15-18-year-old pretest group and the posttest group regarding shooting ability. Keywords: Drill, Practice, Shooting